Aprimoramento do gerenciamento de estoque de um hospital público com a aplicação de técnicas e tecnologias da informação voltadas para mapeamento de processo e inteligência de negócio - SOUZA JUNIOR, José Carlos Couto (2016)
The stock of materials and medicine is needed in hospitals in order to ensure patient care, but this represents between 10% and 18% of net earnings of an institution. Proper management of this stock is necessary so that there are no leaks and the interaction with suppliers can reduce this value, allowing the organization to invest in priority areas. The “Hospital do Subúrbio” identified improvements to be applied in its inventory management and, through the use of information technology resources, has increased knowledge on the subject, making adjustments in their management process, thus reducing the total losses and urgent purchases, tending to reduce the value of fixed inventory. In addition to improving internal processes. By this way, this work proposes to use processes, techniques and technologies in the area of information technology as well as business administration companies, to provide the reduction of fixed assets inventory and optimize the management of materials and medicines of the “Hospital do Subúrbio”. Business Process Management and Business Intelligence resources were used for process mapping and analysis of indicators with the aim of applying certain assumptions of just in time philosophy and reduce the stock of materials and medicines. As a result, there was a reduction of losses, surplus stock and urgent orders, in addition to better structure the supply sector.The results refer to the period from January to March 2016, which were compared to 2015 year data.